Clinical and pathological analysis of dedifferentiated liposarcoma of spermatic cord - Yunji Sun; Fujuan Wang; Zhipeng Yan; Heng Zhang; Baoqun Xu; Maokun Sun (Urology Case Reports, 2025)
The dedifferentiated liposarcoma of spermatic cord is very rare in clinical practice, which usually occurs in middle-aged and elderly men. To improve the understanding and treatment level of dedifferentiated liposarcoma of spermatic cord by sharing the clinical manifestations, imaging features, and pathological characteristics of the rare case. The patient was an elderly man with a left scrotal mass for 2 years. The postoperative pathology was consistent with the pathological features of dedifferentiated liposarcoma. At present, radical orchiectomy is the main treatment method. The successful diagnostic and therapeutic experience of this case can be referenced for clinical practice.